Factors Affecting Income Generation From Cashew Nut Marketing among Marketers in Ogbomoso Agricultural Zone, Oyo State, Nigeria - Adeomi, Damilola Toluse; Akindele, Temitope Joshua; Fajobi, Deborah Tosin; Jubreel, Olasunbo Kafilat; Ojediran, Temitope Janet; Ajibesin, Gbohunmi Damisola (Pancasila International Journal of Applied Social Science, 2025)
The study seeks to investigate factors influencing income generation among cashew nut marketers in Ogbomoso Agricultural Zone, Oyo State. Ninety cashew nut marketers were chosen for the study using a multistage sample procedure, and the data were obtained from the marketers with the aid of a well-structured questionnaire. The data collected were analyzed using descriptive and inferential statistics. From the result, majority of the respondents (88.9%) are male, and 36.7% are middle-aged and active. Additionally, the results indicated that the majority of respondents (91.1%) were married with household size of up to five members.  It was observed that most (37.8%) of the respondent had up to Tertiary education with 97.8% of the respondents taking cashew nut marketing as their primary occupation. Age, marketing experience, transportation and purchase costs were significant factors affecting income generation among cashew nut marketers. The results showed that cashew nut marketers were faced with a number of challenges including low demand, lack of market information, coordination problems, seasonality in supply and demand, and transportation problems.